(untitled) (Research, Society and Development, 2025)
The aim of this study was to describe and analyze the obstacles faced by Physical Education teachers in preparing for the Montes Claros School Games (JEM-MOC) and the Minas Gerais School Games (JEMG). The quantitative research sought to understand the difficulties and methodologies used by the participating teachers. To this end, a structured questionnaire was administered to 37 teachers from different education networks, including municipal, state and private schools, who took part in the JEM-MOC. Data was collected via Google Forms and analyzed using descriptive statistical methods, such as mean and standard deviation, to identify patterns and trends in the responses. The results revealed that the teachers, with an average age of 41.7 years, are mostly male (64.86%) and have completed higher education (91.9%). The majority have more than 10 years’ experience in the area (67.6%) and have already taken part in the JEMG (97.3%), but 94.6% have not received specific training for this activity. In addition, most of them face difficulties in managing and preparing sports teams due to a lack of time and adequate resources for training, as well as a lack of institutional and financial support, since 94.6% do not receive any additional pay for the job. Despite the challenges, teachers recognize the importance of the School Games as a valuable opportunity for students’ social and sporting development.